Posted by
**jessica (the other one)** on
.

Given the function f(x) = x4 , and suppose g(x) is some other function of x.

(a) Then the function F(x) = (g(x))^4 is the same thing as ...

a. f '(g(x)) · g'(x)

b. f(g(x))

c. f '(x)

d. f '(g(x))

e. g(f(x))

(b) By either the extended power or the chain rule, we have F '(x) =

a. g(4x^3)

b. 4 (g(x))^3 · g '(x)

c. 4 (g(x))^3

d. x^4 g'(x) + 4x^3g(x)

e. 4x^3 · g '(x)

(c) It follows that F '(2) =

a. 32(g '(x))

b. 4 · g(8) · g '(2)

c. 4 · (g(2))^3

d. g(32)

e. 4(g(2))^3 · g '(2)

Thanks ya'll!